EFFECT OF DEFOLIANT APPLICATION ON COTTON WEIGHT PER BAG AT DIFFERENT CROP THICKNESSES - Mamatkulov Orifjon Odiljon ogli; Kabilov Sokhib Sherovich (Web of Journals Publishing, 2025)
In cotton farming high to productivity in reaching agrotechnician of events place is incomparable. In particular, the street thickness right designation and applying defoliant technology of cotton quality indicators and harvest to the elements noticeable impact shows. Move Optimal thickness to be of plants growth and development processes balancing, defoliation and cotton of the breasts faster and one in rhythm to the opening help These factors one in the chest cotton weight important in the formation of importance profession will come. So Okay, move. thickness and defoliant application one in the womb cotton to the weight the impact study current scientific and practical importance has is considered.
Keywords: Cotton fruit, fruit weight, electronic scales, seedlings thickness, 1-2 terms, option, default, template, baystar, background.